DR TASSADUQ HUSSAIN (Pakistan Armed Forces Medical Journal, 2022)
Graduated from KEMC, Lahore, (1975); got MPhil from PGMI, Lahore (1983); served in Pakistan and Libya for 41 years in several faculty positions to teach various disciplines of Anatomy, especially the Neuroanatomy and Embryology at both under- & postgraduate levels with the longest spell at CPMC, Lahore, since its inception.